Hybrid Courts and Multilevel Rules of Law: Some Overall Considerations, Challenges and Opportunities - Andersen, Henrik (International Journal of Criminology and Sociology, 2017)
Hybrid courts are the third generation of international criminal bodies. Their hybrid nature makes them distinctive in the international judicial order. They combine domestic and international law; legal infrastructures; personnel at national and international level etc. They are praised in literature for overcoming resource and domestic legal infrastructural challenges and at the same time they stay close to the domestic legal order, and they satisfy the application of international criminal law in the specific cases. In addition, hybrid courts are instrumental in the process of transitional justice towards rule of law based societies. The concept of rule of law is contested. It can vaguely be defined as supremacy of law and it can be approached from various angles. The article claims that rule of law is a moral and/or political maxim with substantive values as it must provide both individuals and the public access to justice; it must provide a degree of equality of the subjects of law; it must provide predictability and legal certainty; it requires transparent procedures and impartial third party dispute mechanisms; and it must ensure the functionality of the legal system. Rule of law is further challenged when it is taken into the statist international sphere and into international criminal law. Where hybrid courts can serve the rule of law, they are also faced with rule of law challenges by governmental interference and by finding a balance between national and international law.